Political body and decolonial criticism: the 1st March of Indigenous Women (PerCursos, 2021)
TThe text is inscribed in the context of the 1st March of Indigenous Women, which took place in August 2019, in the city of Brasília / DF, and proposes a decolonial critical analysis of the gender and ethnic violence that indigenous women experience. It analyzes speeches constructed by traditional and alternative media, as well as interviews given by indigenous women who participated in this movement.  The March was the place that promoted a fissure that is open and reveals the strength of indigenous women as one of the main social movements that question and maintain criticism, essential elements for democracy.
Keywords: Indigenous women; 1st March of Indigenous Women; Representation; Decolonial narrative